Climate shocks and price dynamics: the role of Shinano River in transmitting ENSO effects to Japanese rice markets - Zhu, Haoran (Frontiers in Environmental Science, 2025)
ObjectiveSince 2024, Japan has experienced a rapid surge in rice prices. This study aims to explore the underlying climatic drivers of this price increase, with a particular focus on the potential impact of the El Niño–Southern Oscillation (ENSO).MethodsHigh-frequency climate and market data are integrated, and regression models are constructed in distinct stages along with spatial econometric models to systematically assess the impact of ENSO on Japan’s rice market. The NINO index serves as the primary explanatory variable representing ENSO intensity.ResultsThe findings reveal that ENSO events indirectly affect rice prices in Niigata by altering hydrological conditions in the middle reaches of the Shinano River. These disruptions trigger price co-movement and spatial spillover effects across different regions, resulting in heterogeneous impacts on rice price volatility throughout Japan. Moreover, climate shocks are amplified through hydrological systems in rice-producing areas, ultimately influencing the national grain market.ContributionsThis study provides a natural explanation for recent fluctuations in Japanese rice prices and presents new empirical evidence on the climatic determinants of food price volatility. It also offers actionable policy recommendations to mitigate climate-related risks and enhance food security through climate-responsive agricultural strategies.